Da Mitologia Antiga À Literatura Lobatiana Infanto-Juvenil: Estudo Da Transposição Do Mito Do Herói Hércules - Lima, Giovanna Santos Alves De [UNIFESP] (2017)
This research intends to study the transposition made by Monteiro Lobato from the myth of the hero Hercules in Os Doze Trabalhos de Hercules. Two books are used as basis for this analysis: Heracles, by the greek writer Euripides (IV a.C.) and Metamorphoses (Book IV), by the latin writer Ovid. We take the term “transposition” in the sense of changes made in the semantic field and genre of the text. In this sense, Lobato, who uses ancient sources as basis-texts, transforms the text adapting it to its target audience and its time. To proceed this investigation, we will use the theoretical framework developed by Gérard Genette in his work Palimpsestos. To complement, the concepts of myth in Mircea Eliade and Joseph Campbell will also be used in order to comprehend the Hero‟s Journey presented in the three stories. Taking as the motus of this transtextual analysis, it is intended to verify the ways through which Monteiro Lobato transposes to a narrative structure the story of Hercules and his twelve labors locating them in the universe of Sítio do Picapau Amarelo: there, Pedrinho, Visconde and Emília go back in time to visit the ancient Greece. The reading that is proposed from the adaptation of the greek myth to Lobato‟s narrative intends to analyse its didactic feature and, being so, the author‟s intention. Lobato‟s narrative has as an assignment to teach its target audience, representing not only the story of Hercules, but also several greek myths and aspects of the modern every day life, such as education, friendship and the importance of imagination. Moreover: we can confirm if Lobato keeps the mythical characteristics from Ovid and Euripides‟ works and, if so, which changes were necessary and what are his possible reasons for doing so.